'End-of-life' decision making within intensive care - objective, consistent, defensible?. Issue 6 (1st December 2000) - Ravenscroft, Andrew J; Bell, M D Dominic
Abstract : Objective—To determine the objectivity, consistency and professional unanimity in the initiation, continuation and withdrawal of life-prolonging procedures in intensive care–to determine methods, time-scale for withdrawal and communication with both staff and relatives–to explore any professional unease about legality, morality or professional defensibility. Design—A structured questionnaire directed at clinical nurse managers for intensive care. Setting—All intensive care units in the Yorkshire region. Results—The survey reported a lack of consistency and objectivity in decision making in this area, with accompanying unease amongst staff. Conclusions—There is a need to work towards more consistent care, both before and during admission, for the protection of the individual patient and to allow rational assessment of intensive care need. Comprehensive audit should lead to objective defensible decisions and facilitate informed choice. More open debate and better communication should minimise this issue as a source of stress amongst staff in intensive care.